Flow Cytometric Analysis of Hematopoietic Populations in Rat Bone Marrow. Impact of Trauma and Hemorrhagic Shock. Issue 11 (9th October 2019) - Francis, Wendy R.; Ireland, Rachel E.; Spear, Abigail M.; Jenner, Dominic; Watts, Sarah A.; Kirkman, Emrys; Pallister, Ian
Abstract: Severe injury and hemorrhagic shock (HS) result in multiple changes to hematopoietic differentiation, which contribute to the development of immunosuppression and multiple organ failure (MOF). Understanding the changes that take place during the acute injury phase may help predict which patients will develop MOF and provide potential targets for therapy. Obtaining bone marrow from humans during the acute injury phase is difficult so published data are largely derived from peripheral blood samples, which infer bone marrow changes that reflect the sustained inflammatory response. This preliminary and opportunistic study investigated leucopoietic changes in rat bone marrow 6 h following traumatic injury and HS. Terminally anesthetized male Porton Wistar rats were allocated randomly to receive a sham operation (cannulation with no injury) or femoral fracture and HS. Bone marrow cells were flushed from rat femurs and immunophenotypically stained with specific antibody panels for lymphoid (CD45R, CD127, CD90, and IgM) or myeloid (CD11b, CD45, and RP‐1) lineages. Subsequently, cell populations were fluorescence‐activated cell sorted for morphological assessment. Stage‐specific cell populations were identified using a limited number of antibodies, and leucopoietic changes were determined 6 h following trauma and HS. Myeloid subpopulations could be identified by varying levels CD11b expression, CD45, and RP‐1. Trauma and HS resulted in a significant reduction in total CD11b + myeloid cells including both immature (RP‐1(−)) and mature (RP‐1+) granulocytes. Multiple B‐cell lymphoid subsets were identified. The total percentage of CD90+ subsets remained unchanged following trauma and HS, but there was a reduction in the numbers of maturing CD90(−) cells suggesting movement into the periphery. © 2019 The Authors. Cytometry Part A published by Wiley Periodicals, Inc. on behalf of International Society for Advancement of Cytometry.